A Novel Splice-Site Variation in COL5A1 Causes Keratoconus in an Indian Family. (20th October 2019) - Lin, Qinghong; Zheng, Lin; Shen, Zhengwei; Jie, Liming
Abstract : Objective . This study aims to clarify the association between keratoconus (KC) and potential pathogenic genetic variants in a three-generation South Indian family. Methods . In the present study, a three-generation KC family, which comprised 10 affected patients and nine unaffected individuals, was recruited. The family history and necessary ophthalmological exams, such as visual acuity and slit-lamp, were performed for all participants. Genomic DNA was extracted from peripheral blood leukocytes, and whole exome sequencing (WES) was performed using the genomic DNA of the proband (III:4) and two other family members (III:2, III:3). The acceptor-splice-site mutation was validated and verified using polymerase chain reaction (PCR) and Sanger sequencing. Gene functions and pathways associated with the identified mutations were subjected to in silico analysis. Results . A novel COL5A1 acceptor-splice-site mutation IVS50-4C > G was found in the 10 affected individuals in the three-generation KC family, but this was not found in any of the unaffected family members or unrelated healthy individuals. Gene functional analysis using the SpliceMan and ExonScan software predicted that the splice-site mutation was potentially associated with KC pathogenesis. This mutation might affect the assembly of the collagen triple helix. Conclusion . The present study confirmed the association between the COL5A1 gene and KC and identified a novel COL5A1 acceptor-splice-site mutation (IVS50-4C > G) in intron 50, which may affect the splicing of the adjacent exon 50.